Tranexamic acid is effective in lower doses with infusion in total knee arthroplasty - Aytuluk, Hande Gurbuz (Acta Orthop Traumatol Turc, 2019)
OBJECTIVE: To identify the most effective intravenous regimen with reduced doses of tranexamic acid (TXA). METHODS: We retrospectively evaluated the two most frequently used TXA regimens (infusion and divided-dose regimens) in total knee arthroplasty in comparison with patients not treated with TXA, in three groups. Group NO (n = 134; 19 men and 115 women; mean age: 66.48 ± 7.66) (patients who were not treated with TXA); group DIV (n = 158; 14 men and 144 women; mean age: 65.67 ± 7.98) (total dose of 10 mg/kg intravenous TXA divided into two doses: 15 minutes before tourniquet inflation and 15 minutes before tourniquet deflation), an extra 5 mg/kg intravenous TXA dose was administered 2 hours after surgery in the orthopedic ward, if needed; and group INF (n = 193; 33 men and 160 women; mean age: 67.08 ± 7.2) (10 mg/kg TXA perioperative intravenous infusion starting 15 minutes before surgery until closure of the wound, and 5 mg/kg additional intravenous dose was administered 12 hours after surgery). Pre-postoperative hemoglobin (Hb) and hematocrit (Htc) difference, total blood loss (TBL), number of transfused packed red blood cells (pRBC), and length of hospital stays (LOS) were compared between the groups. RESULTS: TBL was lower in group INF (531.61 ± 316.76 mL) in comparison with group DIV (999.91 ± 352.62 mL). TBL was statistically significantly higher in Group NO (1139.23 ± 43 mL). The mean number of transfused pRBC was significantly higher in the control group (1.22 ± 0.58 units) than the in the other TXA groups. The mean number of transfused pRBC was significantly lower in INF group (0.33 ± 0.56 units) than DIV group (0.75 ± 0.63 units). The number of patients requiring transfusion was significantly lower in INF group (28.5%) than DIV group (65.2%). Group NO had the highest number of patients requiring transfusion (96.3%). Pre-postoperative Hb and Htc difference was significantly lower in INF group (−1.19 ± 0.9 gr/dL and −3.74 ± 2.96%). The mean LOS of the control group, group DIV and group INF were 7.16 ± 2.29, 6.93 ± 2.39 and 5.06 ± 1.24 days, respectively. Group INF had the lowest hospital stay time in comparison with the other groups (p < 0.005). There was no statistically significant difference between the control group and group DIV in the LOS. CONCLUSION: A total dose of 10 mg/kg of TXA perioperative intravenous infusion starting 15 minutes before the surgery until wound closure can significantly decrease TBL. Intraoperative infusion regimen is more effective than the divided-dose regimen. LEVEL OF EVIDENCE: Level III, Therapeutic Study.